1992
DOI: 10.1055/s-2007-1010496
|View full text |Cite
|
Sign up to set email alerts
|

Value of Endoscopic Ultrasonography in the Management of Portal Hypertension

Abstract: Using endoscopic ultrasonography (EUS) a large part of the portal venous system can be visualized. In 40 patients with portal hypertension (PH) and in 48 control subjects EUS displayed the azygos, splenic, mesenteric and portal veins in both groups. However, esophageal and gastric varices, peri- esophageal and peri-gastric collateral veins and submucosal gastric venules were displayed only in patients with PH. EUS was inferior to endoscopy for detecting and grading esophageal varices (p less than 0.0005), but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 0 publications
0
47
0
3
Order By: Relevance
“…PSCV present in the periesophageal, peri-gastric and perirectal areas are easily seen by EUS. [14][15][16][17][18] Veins on the mucosal aspect can cause gastrointestinal luminal bleeding and those outside the wall may cause extraluminal i.e. pleural or peritoneal bleeding.…”
Section: Order Of Appearance Of Collateralmentioning
confidence: 99%
See 1 more Smart Citation
“…PSCV present in the periesophageal, peri-gastric and perirectal areas are easily seen by EUS. [14][15][16][17][18] Veins on the mucosal aspect can cause gastrointestinal luminal bleeding and those outside the wall may cause extraluminal i.e. pleural or peritoneal bleeding.…”
Section: Order Of Appearance Of Collateralmentioning
confidence: 99%
“…Sato et al demonstrated that intramural rectal varices, perirectal collateral veins, and the communicating veins between intramural rectal varices and perirectal collateral veins could be observed clearly via an ultrasonic microprobe. 15,[59][60][61][62] The right colon is drained by three tributaries of SMV, which include the ileocolic, right colic and middle colic veins. Tributaries joining inferior mesenteric vein drain the rest of the colon.…”
Section: Applied Anatomy Of Colonic and Rectal Varicesmentioning
confidence: 99%
“…Endoscopic Ultrasonography (EUS) is a useful modality for the diagnosis for esophagogastric varices [6][7]. With the provision of Doppler capabilities, ECDUS allows the sonographic visualization of the vessels, as well as evaluation of vascular blood flow and morphology [8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasonography (EUS) has become a useful modality for the diagnosis for esophagogastric varices, and it is considered most useful in evaluating gastric varices [27][28][29]. In a previous report, Sato et al described the utility of endoscopic color Doppler ultrasonography (ECDUS) in patients with gastric varices [30].…”
Section: Diagnosis Of Gastric Varices Secondary To Left-sided Portal mentioning
confidence: 99%